Popliteal artery entrapment syndrome: a rare cause of claudication in young athlete - Suraya A; Emy SR; Hamzaini AH; Sharifah MIA; Maizatuljamny M (Department of Surgery, UKM Medical Centre, 2011)
Popliteal artery entrapment syndrome is an important infrequent cause of serious disability among young adults and athletes. We hereby describe a case of popliteal artery syndrome and its clinical implications. Physicians should be aware of the possibility of popliteal artery entrapment in young patients presenting with progressive arterial insufficiency.